2015
DOI: 10.1515/bjdm-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among lower arch length, arch width and arch perimeter in crowding and non-crowding groups

Abstract: SUMMARY Crowding is one of the causes of class I malocclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Based on their study, Janson et al [ 1 ] found that arch length was negatively correlated with dental crowding. As for intercanine and intermolar widths, Selmani et al [ 25 ], as well as Abid et al [ 11 ], reported significantly narrower arch widths in patients with crowding. In their study, Faruqui et al [ 2 ] found no statistical differences in intercanine widths between crowded and non-crowded arches; meanwhile, Ikoma et al [ 26 ] observed that intercanine widths were wider, whereas intermolar widths were not different.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their study, Janson et al [ 1 ] found that arch length was negatively correlated with dental crowding. As for intercanine and intermolar widths, Selmani et al [ 25 ], as well as Abid et al [ 11 ], reported significantly narrower arch widths in patients with crowding. In their study, Faruqui et al [ 2 ] found no statistical differences in intercanine widths between crowded and non-crowded arches; meanwhile, Ikoma et al [ 26 ] observed that intercanine widths were wider, whereas intermolar widths were not different.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this, in our study, there was no significant importance noticed in arch length for the prediction of crowding, while there was a significant difference in sum of incisors between noncrowded and crowded dentition in both the arches in mixed dentition, making it a reliable measurement for the prediction of dental crowding. A study was conducted in 2015 by Selmani and Gjorgova 19 to compare the relationships between the length, width, and perimeter of crowded and uncrowded arches.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are supported by results of studies put forward by Little 21 , Hamid and Rahbar 17 . Dental crowding is caused by various different reasons which includes development or decrement in length of dental arch, maturation, aging of dentition etc 22,23 .…”
Section: Discussionmentioning
confidence: 99%